AL AZHAR SEBAGAI PUSAT PENDIDIKAN FATIMIYAH: ASPEK INSTITUSIONAL, KURIKULUM DAN WARISAN PENDIDIKAN ISLAM DI MESIR (970–1171?M) - Yassir Hafidh Fitriyan; Mutohharun Jinan (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
This study analyzes Al-Azhar during the Fatimid Dynasty (970–1171 CE) as a center of Islamic education that played a significant role in the development of science, theology, and politics. Using a library research method with a descriptive-historical approach, this study examines Al-Azhar's institutional structure, curriculum, and Islamic educational legacy. The results show that Al-Azhar was initially established as a state mosque and served as a means of disseminating Shia Ismaili ideology as well as an educational center that integrated religious knowledge with rational sciences such as logic, philosophy, and astronomy. Support from the Fatimid Caliphate and the waqf (endowment) system were key factors in sustaining the institution's survival. After the fall of the Fatimids, Al-Azhar transformed into an inclusive Sunni educational institution while maintaining its intellectual heritage. This study confirms that Al-Azhar's educational model during the Fatimid era contributed significantly to the emergence of the madrasah system and modern Islamic education, while also providing important lessons on the integration of religious knowledge and science, waqf-based funding, and collaboration between the state and educational institutions. ABSTRAK Penelitian ini menganalisis Al-Azhar pada masa Dinasti Fatimiyah (970–1171 M) sebagai pusat pendidikan Islam yang berperan penting dalam pengembangan ilmu pengetahuan, teologi, dan politik. Menggunakan metode penelitian pustaka dengan pendekatan deskriptif-historis, studi ini mengkaji struktur kelembagaan, kurikulum, serta warisan pendidikan Islam Al-Azhar. Hasil penelitian menunjukkan bahwa Al-Azhar awalnya didirikan sebagai masjid jum‘ah negara dan berfungsi sebagai sarana penyebaran ideologi Syiah Ismailiyah serta pusat pendidikan yang mengintegrasikan ilmu agama dengan sains rasional seperti logika, filsafat, dan astronomi. Dukungan kekhalifahan Fatimiyah dan sistem wakaf (waqf) menjadi faktor utama dalam menopang keberlangsungan lembaga ini. Setelah kejatuhan Fatimiyah, Al-Azhar bertransformasi menjadi lembaga pendidikan Sunni yang inklusif dan tetap mempertahankan warisan intelektualnya. Studi ini menegaskan bahwa model pendidikan Al-Azhar pada masa Fatimiyah berkontribusi besar terhadap lahirnya sistem madrasah dan pendidikan Islam modern, sekaligus memberikan pelajaran penting tentang integrasi ilmu agama dan sains, pendanaan berbasis wakaf, serta kolaborasi antara negara dan lembaga pendidikan.